2022
DOI: 10.1155/2022/8075349
|View full text |Cite|
|
Sign up to set email alerts
|

Influencing Factors and Improvement Path of Synergistic Value Creation Efficiency of Emerging Enterprises

Abstract: The cooperation between emerging enterprises and different enterprises can stimulate innovation enthusiasm and realize synergistic value creation. At present, there is no regular pattern and rules for synergistic value creation among emerging enterprises, which cannot achieve effective synergistic value creation. Based on the complex network relationship and dynamic model of game evolution among multiple entities of value creation within emerging enterprises, the factors that affect the efficiency of synergist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Meanwhile, due to the different strengths of the participating enterprises and their different degrees of contribution in the cooperation, the distribution of profits from the low-carbon technology innovation cooperation will inevitably produce inequitable problems (Gandia & Gardet, 2019;Regan, 2019). Therefore, to sustainably promote low-carbon technology innovation cooperation in industrial clusters, it is necessary to fully coordinate the distribution of cooperation benefits among the participating enterprises (Llamosas & Sovacool, 2021;Liu et al, 2022;Liu et al, 2019). In industrial clusters, the main stakeholders in low carbon technology co-innovation primarily include leading enterprises, supporting enterprises and retail enterprises, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, due to the different strengths of the participating enterprises and their different degrees of contribution in the cooperation, the distribution of profits from the low-carbon technology innovation cooperation will inevitably produce inequitable problems (Gandia & Gardet, 2019;Regan, 2019). Therefore, to sustainably promote low-carbon technology innovation cooperation in industrial clusters, it is necessary to fully coordinate the distribution of cooperation benefits among the participating enterprises (Llamosas & Sovacool, 2021;Liu et al, 2022;Liu et al, 2019). In industrial clusters, the main stakeholders in low carbon technology co-innovation primarily include leading enterprises, supporting enterprises and retail enterprises, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%